Spectrum of Respiratory Involvement in COVID 19 Era; An Overview - Ayushi Jain1 , DhruvTalwar2 , Sunil Kumar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: COVID 19 is novel coronavirus which first struck the world 5 months ago and becamepandemic in such a short time. China suffered first and then this virus spread to more than 180 countries.Primary organ involved is lungs and the commonest cause of fatality is respiratory failure1. Although, itsnew virus, related to two earlier deadly viruses e.g. SARS and MERS but has already caused tremendousmorbidity and mortality in nations heavily affected by it. This short review highlights about lung involvementdue to this virus and to make our healthcare professionals aware about what to expect by learning from theexperience of the countries where it has already affected thousands of civilians.Methodology: This review article was written with systematic literature review with the help of data searchmachine like Pubmed, Scopus, Web of Sciences and google scholar. In this article observational study wandcase reports were included. Most of the data were taken from China, Italy and Spain.Review Findings: COAVID 19 affects lung parenchyma in moderate to severe disease causing pneumoniawhich starts as unilateral lower lobe, commonly on right side, peripheral ground glass infiltrates and rapidlyspreads to involve both lungs with bilateral, multifocal consolidations2. Pleural effusion and pericardialinvolvement may occur. In severe cases the disease progresses to Acute Respiratory Distress Syndromeaccounting for >90% of mortality. Pathology of lungs showed diffuse alveolar damage with organizationand fibrosis as disease progresses.Conclusions: COVID 19 a novel coronavirus which is presently a pandemic has affected the world in mannerreminiscence of 1918 Spanish flu. Lung involvement as community acquired pneumonia is determinant ofmortality, which spreads exponentially to develop sever respiratory failure